Spatial analysis of COVID-19 in North Minahasa Regency of North Sulawesi Province - Kandou, Grace D.; Ratag, Budi T.; Sekeon, Sekplin A. S.; Kandou, Priscilla C. (International Journal Of Community Medicine And Public Health, 2021)
Background: COVID-19 is an infectious disease that is currently a concern and has become a global problem. The trend in the number of confirmed cases and deaths due to COVID-19 every day is still increasing significantly. North Sulawesi Province currently has 7 regencies/cities which are declared as local transmission areas including North Minahasa Regency. The population density factor can affect the process of transmission of this disease. This study aims to determine the spatial description of the distribution of COVID-19 events in North Minahasa Regency. Methods: This quantitative research with descriptive observational design using a geographic information system approach. The location is in 10 sub-districts of North Minahasa Regency. Study population was all patients who were confirmed positive for COVID-19 based on data from the North Minahasa District Health Office as of 13 February 2021, as many as 1,273 cases. Simple random sampling was used and obtained 300 samples. Results: Results showed that the highest number of cases was for the age group 30-49 years (40%), female gender (54.7%), symptom onset date interval 4 days (26.7%), confirmation date grouped by month, namely October in 2020 (23%), the status of the patient recovered (86%), and there were no comorbidities (82%). Conclusions: Most of the cases of COVID-19 were found in densely populated areas and passenger transit areas between districts/cities. Policies on prevention and supervision of health protocols that are implemented must synergize across sectors and need to be improved.